TOURISM DESTINATION BRANDING: ANALISIS STRATEGI BRANDING WISATA HALAL “THE LIGHT OF ACEH” (Studi Kasus pada Dinas Kebudayaan dan Pariwisata Aceh Tahun 2015-2016) - Desi Maulida (Universitas Teuku Umar, 2019)
Strategy of tourism destination branding is an important factor in the the process of tourism development of a region. As well as it happens in Aceh, which is the only province in Indonesia applying the islamic sharia. The purpose of this study is to determine and analyze the strategy of destination branding conducted by Department of Culture and Tourism in Aceh. The strategy is started from the vision and stakeholder management, target consumer and portfolio matching, positioning and differentiation strategies using brand components, communication strategies, feedback and response management strategies. The theory used to analyze this strategy is the theoretical principles of tourism destination branding. This study is qualitative descriptive with the case study method. Data collecting method is conducted through in-depth interviews with 8 informants coming from branding team, observations and documentation. The result shows that the strategy undertaken by Department of Culture and Tourism with the branding team of Aceh has been going well, especially in the marketing communication activity. It was marked with a plenty of program related to the implementation of marketing, either using print media, electronic media, billboards, and internet media, especially social media. However, in the branding activity, there are actually some obstacles should be faced, such as the industry player which is less cooperative to provide halal certification for an aprecondition for halal tourism, lack of budget allocation, and the low awareness of public participation. Therefore, more socialization is needed for the players of tourism industry and also the community to raise their awareness and responsibilty in order to jointly support the development of Aceh tourism.